2015
DOI: 10.1080/15384047.2014.1002366
|View full text |Cite
|
Sign up to set email alerts
|

Metformin: a modulator of bevacizumab activity in cancer? A case report

Abstract: Recurrent type I endometrial cancer ( EC ) has poor prognosis and demands novel therapeutic approaches. Bevacizumab, a VEGF-A neutralizing monoclonal antibody, has shown clinical activity in this setting. To our knowledge, however, although some diabetic cancer patients treated with bevacizumab may also take metformin, whether metformin modulates response to anti-VEGF therapy has not yet been investigated. Here, we report the case of a patient with advanced EC treated, among other drugs, with bevacizumab in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…Cancer is a disease with a growing mortality worldwide, with an increase to 19.3 million new cancer cases per year predicted in 2025. 63 Targeted therapies have achieved notable success in some cancers; however, significant problems including resistance and high toxicity remain to be solved. To address these limits, combining targeted drugs with known drugs has drawn considerable attention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer is a disease with a growing mortality worldwide, with an increase to 19.3 million new cancer cases per year predicted in 2025. 63 Targeted therapies have achieved notable success in some cancers; however, significant problems including resistance and high toxicity remain to be solved. To address these limits, combining targeted drugs with known drugs has drawn considerable attention.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, bevacizumab is widely used to treat various cancers, including advanced nonsquamous NSCLC, metastatic breast cancer, advanced renal cell carcinoma, and advanced epithelial ovarian cancer . A case report showed that bevacizumab combined with metformin in recurrent type I endometrial cancer improved patient performance status: computed tomography scans showed reduced radiologic density of the lung and mediastinal lesions of liver disease, suggesting increased tumor necrosis . Moreover, combining bevacizumab with metformin was also found to be effective in ovarian cancer treatment, Metformin could specifically target cancer stem cells and synergistically inhibits angiogenesis with bevacizumab …”
Section: Combination Of Metformin With Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these limitations, this clinical case suggests that metformin is potentially beneficial in the prevention or treatment of EC. This finding deserves further validation in clinical studies (14)(15)(16). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, sequential or simultaneous combination of antiangiogenic drugs and metformin might represent a new treatment opportunity for LKB1-deficient tumors. Although clinical and preclinical data are fragmentary, a case of a terminally ill patient with advanced endometrial cancer, showing radiological response to simultaneous administration of metformin and bevacizumab, was described by our group [75]. Interestingly, the high expression of MCT4—a marker of enhanced glycolysis—and loss of LKB1 expression were detected in the patient's liver metastasis sample.…”
Section: Targeting the Lkb1-ampk Pathwaymentioning
confidence: 99%